Academic Brands - Biagioli, Mario; Sunder, Madhavi (Social Sciences, 2022)
Universities are increasingly presenting tas brands in their global marketing efforts. This volume shows what the emergence of academic brands can teach us about the rise of the 'university of excellence,' its global spread, and managerial values and marketing practices in higher education. Available as Open Access on Cambridge Core.